Indonesian Muslim Societies in the Digital Age: Opportunities, Challenges, and Future Prospects - Mukhlis; Wardiman, Doki; Yetri, Amelia (Digital Muslim Review, 2024)
The digital era has revolutionised daily life by integrating work, education, communication, entertainment, and commerce. This shift profoundly affects communities with strong cultural and religious identities, such as Muslims in Indonesia. This study explores the opportunities and challenges faced by Indonesian Muslims in adapting to digital transformation. Key challenges include limited technology access, ethical concerns in digital content, and potential threats to religious and cultural identity. Employing a qualitative approach with descriptive analysis, the study finds that digital technology improves educational access, fosters economic growth through e-commerce, and strengthens Islamic da’wah. However, digital inequality, moral dilemmas, and cultural erosion remain pressing issues. To address these, strategic recommendations include enhancing digital literacy, creating relevant Islamic content, leveraging social media for da’wah, and promoting innovation in Islamic business. These findings aim to help Indonesian Muslims navigate the digital era while preserving their religious and cultural values.